Parental Involvement and Its Influence on Academic Achievement: A Cross-Cultural Analysis - Björn Thórsson; Sigrún Ólafsdóttir (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article explores the influence of parental involvement on students' academic achievement across various cultural contexts. By comparing involvement strategies in different countries, the study examines how cultural factors impact parental roles in children's education. Findings indicate that parental engagement significantly boosts academic performance, although the effectiveness of different engagement strategies varies based on cultural norms, socioeconomic status, and parental education levels.